2021
DOI: 10.1016/j.ijregi.2021.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of influenza in Osaka, Japan during the COVID-19 outbreak: a population-based ORION registry study

Abstract: Objectives The spread of COVID-19 has affected the incidence of other infectious diseases, but there are no reports evaluating the impact of COVID-19 on influenza incidence using comprehensive regional population-based data. We attempted to evaluate the impact of COVID-19 on influenza using the population-based ORION (Osaka Emergency Information Research Intelligent Operation Network) registry. Methods Osaka Prefecture developed the ORION registry of emergency patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Switzerland had an unprecedented complete absence of pediatric enteroviral meningitis in 2020 [ 60 ]. In Japan, community-acquired pneumonia [ 61 ] and influenza [ 62 ] admissions have reduced during the COVID-19 pandemic. COVID-19 preventative actions and better personal hygiene are beneficial for preventing the spread of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Switzerland had an unprecedented complete absence of pediatric enteroviral meningitis in 2020 [ 60 ]. In Japan, community-acquired pneumonia [ 61 ] and influenza [ 62 ] admissions have reduced during the COVID-19 pandemic. COVID-19 preventative actions and better personal hygiene are beneficial for preventing the spread of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Switzerland had an unprecedented complete absence of pediatric enteroviral meningitis in 2020 (Stoffel et al, 2021). In Japan, community-acquired pneumonia (Yan et al, 2022) and influenza (Hirose et al, 2021) admissions have been reduced during the COVID-19 pandemic. COVID-19 preventative actions and better personal hygiene are beneficial for preventing the spread of disease.…”
Section: Discussionmentioning
confidence: 99%
“…There were also no differences in the number of deaths of emergency patients admitted to hospital in the analyses by reason for ambulance call or by age group. Indeed, several previous studies have reported that COVID-19 outbreaks have reduced emergency patients due to influenza and mortality due to other infectious diseases [ 23 , 24 ]. On the other hand, there were concerns that other acute illnesses might affect the prognosis of emergency elderly patients due to an increase in demand for medical care.…”
Section: Discussionmentioning
confidence: 99%